The clinical course of non-muscle invasive bladder cancer after transuretral resection of the tumor with or without subsequent intravesical application of bacillus Calmette-Guérin: The influence of patients gender and age - Milošević Radovan; Milović Novak; Aleksić Predrag; Lazić Miodrag; Cerović Snežana; Prelević Rade; Spasić Aleksandar; Simić Dejan; Kovačević Božidar (Vojnosanitetski Pregled)
Bacground/Aim. The therapy with intravesical instillation of bacillus Calmette-Guérin (BCG) after transurethral resection (TUR) of tumor is the gold standard of treatment of non-muscle invasive bladder cancer (NMIBC). The role and importance of BCG intravesical therapy in various shape of tumors, were confirmed by our previous investigation. The aim of this study was to examine whether incidence of recurrence and tumor regression differs depending on sex and age of patients. Methods. This study included a total of 899 patients suffering from NIMBC, treated at our institution from January 1, 2007 to March 1, 2013. Two groups of patients were formed: patients underwent TUR + BCG therapy (the group I) and the group II with patients in whom TUR was performed as only therapy. These two groups of patients were divided into subgroups of respondents male and female, age 60 years or younger and older than 60 years. Statistical analysis was performed using χ2 test and the Kolmogorov-Smirnov test. Results. This research suggests that if the frequency of recurrence is seen as the only parameter, considering all the subjects, the lowest recurrence rate was determined in the male subjects, aged 60 years and younger who had received BCG after TUR. A high statistical significance was found in the incidence of recurrence in patients younger than 60 years, depending on the response to the therapy, while in those older than 60 years, the difference was at the level of statistical significance. This can be attributed to a certain degree of infravesical obstruction in older men. Conclusions. Sex and age of patients may have a significant influence on the course and outcome of NMIBC. The disease has the most malignant and most aggressive behavior when present in males older than 60 years.